I-Learn, futuristic platform of Islamic knowledge based society - Ahmad Dahlan, Abdul Rahman; Salehi, Sayed Kabir; Mohammed Abdulrahman Ali, Sami; Tarek Elgammal, Mohamed (IJSRP.ORG, 2016)
This paper aims to focus on the introduction of the eLearning systems and the importance of the eLearning systems among the today community, globally. Besides that, it will be also discussed the concept of distance learning and its place in todays’ world. Furthermore, at the peak, it will be the introduction of the Islamic eLearning system called iLearn which is being proposed as an ultimate solution for the Islamic based society as comprehend way to manage knowledge in accordance with Islamic thoughts and values. I-learn is an outstanding platform created to meet the need of today’s Islamic World education concerns. The idea comes after the appearance and growth of numerous e-learning networks which enables the individuals to study and learn online. Despite the fact that there are number of e-learning websites with Islamic nature, yet there are several gaps which needs to be filled by our initials.